Beta-sitosterol induces apoptosis in MCF-7 cells - Chai, J.W.; Kuppusamy, U.R.; Kanthimathi, M.S. (2008)
Cyrtandra cupulata Ridl. (Gesneriaceae) is local medicinal plant, also known as âBebangunâ or âKabutâ by the East Malaysian Ibans. It is indicated for post partum malaise and known to be an abortifacient, among other uses. Î²-Sitosterol is a known phytoestrogen with many reported bioactivities including anticancer. This study examined the effect of Î²-sitosterol isolated from C. cupulata through bioactivity-guided purification monitored by the growth inhibitory effect on MCF-7, an estrogen receptorpositive breast cancer cell line. Our results demonstrated that Î²-sitosterol dose-dependently inhibited the growth of MCF-7 cells. Treated cells showed a 1.53-fold increase of DEVDase activity, indicating elevated caspase activity. Thus, the growth inhibitory effect of Î²-sitosterol isolated from C. cupulata appeared to be mediated by caspase-induced apoptosis.